A qualitative exploration of techniques used by expert midwives to preserve the perineum intact. Issue 1 (February 2019) - Begley, C.; Guilliland, K.; Dixon, L.; Reilly, M.; Keegan, C.; McCann, C.; Smith, V.
Abstract: Background: The perineum stretches during birth to allow passage of the baby, but 85% of women sustain some degree of perineal trauma during childbirth, which is painful post-partum. Episiotomy rates vary significantly, with some countries having rates of >60%. Recent Irish and New Zealand studies showed lower severe perineal trauma and episiotomy rates than other countries. Aim: To explore expert Irish and New Zealand midwives' views of the skills that they employ in preserving the perineum intact during spontaneous vaginal birth. Methods: Following ethical approval a qualitative, descriptive study was undertaken. Semi-structured, recorded, interviews were transcribed and analysed using the constant comparative method. Expert midwives employed in New Zealand and one setting in Ireland, were invited to join the study. "Expert" was defined as achieving, in the preceding 3.5 years, an episiotomy rate for nulliparous women of <11.8%, a 'no suture' rate of 40% or greater, and a severe perineal tear rate of <3.2%. Twenty-one midwives consented to join the study. Results: Four core themes emerged: 'Calm, controlled birth', 'Position and techniques in early second stage', 'Hands on or off?' and 'Slow, blow and breathe the baby out.' Using the techniques described enabled these midwives to achieve rates, in nulliparous women, of 3.91% for episiotomy, 59.24% for 'no sutures', and 1.08% for serious lacerations. Conclusions: This study provides further understanding of the techniques used by expert midwives at birth. These findings, combined with existing quantitative research, increases the evidence on how to preserve the perineum intact during spontaneous birth.